Establishment of control system for coordinated feeding with liquid pesticide and planting material into the operational section of agricultural crops protectant, is grounded - І. В. Колесник (Plant Varieties Studying and Protection)
Investigational development of modern treater seed of agricultural cultures status. The analysis of efficiency of work control the system modem treater seed is conducted. The ground of creation of cont rol the system by the concerted serve working liquid (liquid poison) and seed is conducted in the working area of treate.